PROSEDUR ADMINISTRASI PENJUALAN PADA USAHA JAYA TEKNIKA JAKARTA BARAT - wijaya, Darma; IRAWAN, ROY (www.bsi.ac.id, 2018)
Abstract- Many factors in addition to promotional efforts, including in terms of service, price matching, also part of the leadership of the company to follow sales orders that are still open. Usaha Jaya Teknika is a company engaged in the sale bearing activities associated with the sale. In bearing sales companies, the administration is required to support continuation of work productivity. One supporting of the labor productivity is sales administration, because sales are very important role among other activities. Customers most influential people in sales, because of the customer and the sales process will occur reciprocal relationship mutual benefit. By this author tries to make the final administrative procedures regarding the sale of Usaha Jaya Teknika, West Jakarta. Therefore, the administrative procedures are very important for the customer sales, because sales administrative procedures to facilitate the sales order. With the sales of structured procedure the customers will be fulfilled. KeyWords: Administrative Procedures, Sales